Academic research the impact of organizational culture on the performance of the internal – study in government institutions- analysis study on some government institutions in state of Qatar - محمد عمر محجوب (Journal of Economics and Administrative Sciences, 2018)
This study was aimed to explore the impact of social concepts about tribe, clan and women, on internal audit performance. These concepts are considered to be components of the organizational culture and performance of internal audit practice, with respect to the individual and collective performance within the institution. The study, furthermore, was intended to investigate and understand the role of the organizational culture of the tribal, clan and women components with regard to their role in society, in Qatar. To achieve these objectives, the researcher followed the descriptive analytical approach, using a questionnaire directed to experts and staff working in the banking sector, with the view to test the hypotheses of the study. The analysis of the data collected revealed that there is no impact of the components of the prevalent culture of the tribe, clan and women on the performance of internal audit, with regard the performance of individuals or collective members of the organization. This indicates that the culture prevalent in the organization surpasses the social misconceptions about the role of tribe, clan and women in the field of public action, it confirms, furthermore, the commitment career and labor regulations and professional conduct. This commitment led to the success of the internal audit role within government and private institutions. Therefore, if the organization is to succeed it should promote and maintain a culture far from negative social influences surrounding the organization.